Combined tumor plus nontumor interim FDG‐PET parameters are prognostic for response to chemoradiation in squamous cell esophageal cancer. Issue 5 (19th February 2020) - Zschaeck, Sebastian; Li, Yimin; Bütof, Rebecca; Lili, Chen; Hua, Wu; Troost, Esther C.G.; Beck, Marcus; Amthauer, Holger; Kaul, David; Kotzerke, Jörg; Baur, Alexander D.J.; Ghadjar, Pirus; et al.
Abstract : We have investigated the prognostic value of two novel interim 18 F‐fluorodeoxyglucose positron emission tomography (FDG‐PET) parameters in patients undergoing chemoradiation (CRT) for esophageal squamous cell carcinoma (ESCC): one tumor parameter (maximal standardized uptake ratio rSUR) and one normal tissue parameter (change of FDG uptake within irradiated nontumor‐affected esophagus ∆ SUVNTO ). PET data of 134 European and Chinese patients were analyzed. Parameter establishment was based on 36 patients undergoing preoperative CRT plus surgery, validation was performed in 98 patients receiving definitive CRT. Patients received PET imaging prior and during fourth week of CRT. Clinical parameters, baseline PET parameters, and interim PET parameters (rSUR and ∆ SUVNTO ) were analyzed and compared to event‐free survival (EFS), overall survival (OS), loco‐regional control (LRC) and freedom from distant metastases (FFDM). Combining rSUR and ∆ SUVNTO revealed a strong prognostic impact on EFS, OS, LRC and FFDM in patients undergoing preoperative CRT. In the definitive CRT cohort, univariate analysis with respect to EFS revealed several staging plus both previously established interim PET parameters as significant prognostic factors. Multivariate analyses revealed only rSUR and ∆ SUVNTO as independent prognostic factors ( p = 0.003, p = 0.008). Combination of these parameters with the cutoff established in preoperative CRT revealed excellent discrimination of patients with a long or short EFS (73% vs . 17% at 2 years, respectively) and significantly discriminated all other endpoints (OS, p < 0.001; LRC, p < 0.001; FFDM, p = 0.02), even in subgroups. Combined use of interim FDG‐PET derived parameters ∆ SUVNTO and rSUR seems to have predictive potential, allowing to select responders for definitive CRT and omission of surgery. Abstract : What's new? In advanced esophageal cancer, preoperative chemoradiation (pCRT) improves survival compared to surgery alone, but it's not clear whether this strategy produces better outcomes than definitive chemoradiation (dCRT). Positron emission tomography scanning can potentially predict the response to CRT using various parameters. In this study, the authors evaluated the prognostic value of two parameters of FDG‐PET. They looked at 134 patients receiving either pCRT plus surgery or dCRT. Screening with these parameters, they found, could successfully identify those patients that would respond best to definitive chemoradiation, and potentially avoid surgery.